The Influence of Principal Leadership Style and Pedagogic Competency on Teacher Performance in Creating Learning Media - Syariefah, Dewi Rini; Santi, Norma; Supriyadi , Supriyadi (International Journal of Business, Law, and Education, 2025)
This study aims to analyze the influence of the principal's leadership style and pedagogical competence on teacher performance in creating learning media at PAUD institutions in Penggilingan Village, Cakung, East Jakarta. This study uses a quantitative approach with a survey method. The research sample consisted of 120 teachers selected using random sampling techniques. Data were collected through a questionnaire that measured the principal's leadership style, teacher pedagogical competence, and teacher performance in creating learning media. Data analysis used correlation and regression techniques. The results showed that there was a positive and significant correlation between the principal's leadership style and pedagogical competence with teacher performance in creating learning media. This indicates that a democratic leadership style and high pedagogical competence contribute to improving teachers' abilities in developing innovative and effective learning media.